Engaging community-dwelling older adults in fall prevention programs: a qualitative study on strategies promoting participation in fall prevention programs among community-dwelling older adults - van Scherpenseel, Meike; van Veenendaal, Lidia; Donné, Lennie; te Velde, Saskia; Ronteltap, Amber (Frontiers in Public Health, 2023)
Introduction Fall rates and fall-related injuries among community-dwelling older adults (≥65 years) are expected to increase rapidly, due to the aging population worldwide. Fall prevention programs (FPPs), consisting of strength and balance exercises, have been proven effective in reducing fall rates among older adults. However, these FPPs have not reached their full potential as most programs are under-enrolled. Therefore, this study aims to identify promising strategies that promote participation in FPPs among community-dwelling older adults. Methods This is an exploratory qualitative study. Previously, barriers and facilitators for participation in FPPs by older adults had been identified. Next, six strategies had been designed using the Intervention Mapping approach: (1) reframing; (2) informing about benefits; (3) raising awareness of risks; (4) involving social environment; (5) offering tailored intervention; (6) arranging practicalities. Strategies were validated during semi-structured interviews with community-dwelling older adults (n = 12) at risk of falling. Interviews were audio-recorded, transcribed, and analyzed following a qualitative thematic methodology, with a hybrid approach. Results All strategies were considered important by at least some of the respondents. However, two strategies stood out: (1) reframing ‘aging’ and ‘fall prevention’: respondents preferred to be approached differently, taking a ‘life course’ perspective about falls, and avoiding confronting words; and (2) ‘informing about benefits’ (e.g., ‘living independently for longer’); which was mentioned to improve the understanding of the relevance of participating in FPPs. Other strategies were considered important to take into account too, but opinions varied more strongly. Discussion This study provides insight into potential strategies to stimulate older adults to participate in FPPs. Results suggest that reframing ‘aging’ and ‘fall prevention’ may facilitate the dialogue about fall prevention, by communicating differently about the topic, for example ‘staying fit and healthy’, while focusing on the benefits of participating in FPPs. Gaining insight into the strategies’ effectiveness and working mechanisms is an area for future research. This could lead to practical recommendations and help professionals to enhance older adults’ participation in FPPs. Currently, the strategies are further developed to be applied and evaluated for effectiveness in multiple field labs in a central Dutch region (Utrecht).